'Blinded by the Desire of Riches': Corruption, Anger and Resolution in the Two‐Part Notre Dame Conductus Repertory. (1st April 2019) - WOODWARD, REBEKAH E.
ABSTRACT: This article examines anger and one of the ways it was expressed by the secular clergy at Notre Dame Cathedral in Paris in the late twelfth and early thirteenth centuries. Applying Barbara Rosenwein's idea of an 'emotional community' to the secular clergy, I consider what we know about the authors and composers of the mostly anonymous conductus repertory and how these men might have acceptably expressed their anger at wrongdoing in the Church. I also examine George Lakoff and Zoltán Kövecses's responses to anger and discuss how the secular clergy react to feelings of anger through non‐prototypical responses. I examine briefly the texts of the nineteen two‐part conductus without melismas in the manuscript Florence, Biblioteca Medicea‐Laurenziana, Pluteus 29.1 (F ), before focusing on five of these conductus, the texts of which convey anger. An analysis of the frequency and use of intervals in these works places their composition at the time when the celebrated theologian Peter the Chanter and his students were at Notre Dame; in addition, it demonstrates the way that intervals highlight significant words that convey the angry theme of the text. I also discuss the use of descending melodic motives, one of which occurs most frequently in the conductus with texts that express anger.